Genome-wide association study of plant color in Sorghum bicolor - Wang, Lihua; Tu, Wenmiao; Jin, Peng; Liu, Yanlong; Du, Junli; Zheng, Jiacheng; Wang, Yi-Hong; Li, Jieqin (Frontiers in Plant Science, 2024)
Sorghum plant color is the leaf sheath/leaf color and is associated with seed color, tannin and phenol content, head blight disease incidence and phytoalexin production. In this study, we evaluated plant color of the sorghum mini core collection by scoring leaf sheath/leaf color at maturity as tan, red or purple across three testing environments and performed genome wide association mapping (GWAS) with 6,094,317 SNPs markers. Eight loci, one each on chromosomes 1, 2, 4, and 6 and two on chromosomes 5 and 9 were mapped. All loci contained 1-3 candidate genes. In qPC5-1, Sobic.005G165632 and Sobic.005G165700 located in the same linkage disequilibrium (LD) block. In qPC6, Sobic.006G149650 and Sobic.006G149700 located in the different LD block. Only one obvious peak showed in the Sobic.006G149700 which was a senescence regulator. We found a loose correlation between the degree of linkage and tissue/organ expression of the underlying genes possibly related to plant color phenotype. Allele analysis indicated that none of the linked SNPs can differentiate between red and purple accessions while all linked SNPs can differentiate tan from red/purple accessions. The candidate genes and SNP markers may facilitate the elucidation of plant color development as well as molecular plant breeding.